(untitled) (Doctor Virtualis, 2008)
La teologia come scienza nel Commento alle Sentenze. La discussione sulla trinità risale a conclusioni teologiche a partire dalla conoscenza sensibile. The theology as science in the Commentary to the Sentences . The discussion about trinity goes up to theological conclusions starting by the sensitive knowledge.